DIABETIC WOUNDS –WHY FOOT ONLY? - Rashmi TM; Sathish HS (International Journal of Applied Ayurved Research, 2017)
Diabetic complications have become inevitable even after so much of innovation in the field of medicine. More than 15% diabetic patients during their lifetime will get macro or microvascular complications. As per contemporary science it was in the period between 1850 & 1870 both gangrene and plantar ulcers were recognized as complications of diabetes. The earliest record of foot t complications in a diabetic individual was in Sushruta’s treatise and it also contains the reason for it. Vascular pathological phenomenon behind the highest incidence of foot complications among diabetics demonstrates the finest observation of Sushruta. Durbalata specifically refers to pathological changes in the vessel, which impairs the vascular function of nutrition and drainage. Vascular pathology being the root cause for complications in foot region is explained in just two words as “Rasayani Dourbalya.”